2014
DOI: 10.9734/bjmmr/2014/5161
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Overfeeding Induced by Reducing the Litter Size Leads to an Obese Phenotype and Increases Preference for Sweet Food in Adult Male Rats

Abstract: Aim: the aim of this study was to induce obesity in rats using the neonatal overfeeding protocol and evaluate in adult male animals standard chow intake, sweet food intake, the preference between sweet food and standard chow, locomotor activity and anxiety-like behavior. Methodology: The neonatal overfeeding protocol consisted of reducing the litter size to 4 animals (small litters = SL) compared to 8 animals in normal litters (NL). In these experiments we used 55 offspring from 18 litters. Results: obesity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It was reported that DRD1 in NAcSh regulates the response to novel stimuli [43] and that intracisternal infusions of DRD1 antagonists blunt the rewarding effects [44,45] and modulate the intake [46,47] of palatable food. Other authors have also reported a greater preference for sweet foods in adult SL animals [48]. Unfortunately, they did not show molecular changes that might be involved in this preference.…”
Section: Discussionmentioning
confidence: 85%
“…It was reported that DRD1 in NAcSh regulates the response to novel stimuli [43] and that intracisternal infusions of DRD1 antagonists blunt the rewarding effects [44,45] and modulate the intake [46,47] of palatable food. Other authors have also reported a greater preference for sweet foods in adult SL animals [48]. Unfortunately, they did not show molecular changes that might be involved in this preference.…”
Section: Discussionmentioning
confidence: 85%
“…In fact, Eisenstein et al found that emotional eating was associated with striatal dopamine D2/D3 binding[93] and Volkow et al found that striatal dopamine response to foods was associated with restrained and emotional eating but not to external eating[94]. Also, in animal research, early life overnutrition has been found to increase dopaminergic precursors and to affect appetite for palatable foods[95, 96], similarly for prenatal undernutrition[11, 12, 97]. In general, low birth weight girls/women seem to be more vulnerable to the effects of prenatal programming of food preferences, showing increased preference for carbohydrates, impulsivity for sugar and emotional overeating when compared no normal birth weight counterparts[10, 13, 98].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature from animal research has showed important effects of early life low and high birth weights on feeding behavior, appetite and physical activity[12, 95, 100103]. A recent systematic review addressing the effects of birth weight on energetic metabolism associated behaviors in humans, such as physical activity, energetic intake, and some aspects of feeding behavior[104], did not find much evidence in the literature for such associations, except for decreased physical activity levels in both extremes of birth weight.…”
Section: Discussionmentioning
confidence: 99%